Preconceito e homofobia contra meninos no ambiente escolar: Engole o choro! Vira homem! Fala direito! - Vieira, André Ribeiro (2024)
This research aims to verify and categorize the existence of possible homophobic behavioral tendencies directed toward male students whose existence does not exactly align with the normative model of "boy," meaning individuals who do not behave or perform according to what the social group understands as "masculine" or "virile." These individuals, from the group's perspective, would represent a future threat to the binary gender order present in society as it stands today, thereby undergoing a process ofstigmatization and prejudice during their school years for deviating from the expected norms. The subjects of this study are teachers from educational units under the Secretaria Municipal de Educação de São Paulo, asthe aim is to characterize potential homophobic actions directed by them toward boys aged 6 to 11 years, students between the 1st and 5th grades of elementary school, an age at which inculcation, introjections, and prohibitions are easily absorbed by the individual. The conceptual framework involves studies and research on prejudice and homophobia from the perspective of critical theory authors. The hypothesis is that, even at the end of the first quarter of the 21st century, school still represents an institutionalized social environment for the reproduction of prejudice and reinforcement of the castration of the figure identified as the "effeminate boy," with homofobia expressing itself through prejudiced behaviors in the school environment. A sample of 151 individuals responded to a questionnaire that included a Likert[1]type attitude scale adapted to measure blatant and subtle homophobia, and six individuals – two men and three women – with diverse sexual orientations were interviewed. The descriptive analysis of the results points to a concerning scenario: most participants perceive that there is homophobic behavior from many adults toward students, and that the social control of bodies to ensure conformity to gender standards in schoolsis stronger for boys than for girls. Furthermore, the analysis of the attitude scaledata demonstrated that the means of exercising homophobia in the school environment are characterized more by a tendency toward refinement, subtlety, and dissimulation than by overt manifestations of prejudice